Towards an ontology for toponyms in Nepalese historical documents - Tittel, Sabine (Workshop on resources and technologies for indigenous, endangered and lesser-resourced languages in Eurasia (EURALIE), 2022)
Nepalese historical legal documents contain a plethora of valuable information on the history of what is today Nepal. An empirical study based on such documents enables a deep understanding of religion and ritual, legal practice, rulership, and many other aspects of the society through time. The aim of the research project `Documents on the History of Religion and Law of Pre-modern Nepal' is to make accessible a text corpus with 18 th to 20 th century documents both through cataloging and digital text editions, building a database called Documenta Nepalica. However, the lack of interoperability with other resources hampers its seamless integration into broader research contexts. To address this problem, we target the modeling of the Documenta Nepalica as Linked Data. This paper presents one module of this larger endeavour: It describes a proof of concept for an ontology for Nepalese toponyms that provides the means to classify toponyms attested in the documents and to model their entanglement with other toponyms, persons, events, and time. The ontology integrates and extends standard ontologies and increases interoperability through aligning the ontology individuals to the respective entries of geographic authority files such as GeoNames. Also, we establish a mapping of the individuals to DBpedia entities.